Strategic Communication of Superordinate Identity in International Marketing: Evidence from Malaysia Madani to Reduce Indonesian Tourism Avoidance - Nirwana, Maya Diah; Kriyantono, Rachmat; Mashuri , Ali; Hakim , Muhammad Lukman (APMBA (Asia Pacific Management and Business Application), 2025)
Cross-border tourism in Southeast Asia is often hindered by identity-based biases and intergroup animosity, particularly towards immigrant communities. Grounded in Social Identity Theory, this study investigates whether the strategic communication of a superordinate identity framed through Malaysia’s inclusive Malaysia Madani campaign can reduce Indonesian tourism avoidance among Malaysian youth. A one-way between-subjects experimental design was implemented with 92 university students (aged 18–24), randomly assigned to either a treatment group exposed to Malaysia Madani narratives or a control group completing a neutral activity. Participants assessed immigrant population threat, immigrant animosity, cultural openness, perceived authenticity communication, and tourism avoidance using validated 7-point Likert scales. Findings revealed that superordinate identity exerted statistically significant but theoretically inconsistent effects on tourism avoidance via threat or animosity. However, cultural openness significantly moderated the relationship between identity and tourism avoidance, whereas authenticity communication did not. These results underscore the pivotal role of cultural openness in international marketing communication strategies aimed at reducing tourism resistance. Theoretically, the study advances identity-based marketing discourse; practically, it suggests that professionals in marketing and tourism should design campaigns that strengthen inclusive identity and foster openness to re-engage reluctant travellers and revitalise regional tourism.